ASUPAN ENERGI DAN AKTIVITAS FISIK BERHUBUNGAN DENGAN Z-SCORE IMT/U ANAK SEKOLAH DASAR DI DAERAH PERDESAAN - Nyoman Wahyu Meta Wulandari; Lailatul Muniroh; Triska Susila Nindya (Media Gizi Indonesia, 2015)
Overweight and obesity can occur at any stages in life, one of them is in primary schoolchildren. Prevalence of overnutrition in schoolchildren rise about 10,85% from 2007 until 2013. This problem not only occurs in urban but also in rural areas. One of the factor is imbalance energy intake and physical activity. The purpose of this study was to analyze the correlation between energy intake and physical activity with z-score of BMI for age among primary schoolchildren in rural area of Penebel Tabanan district. This study was an observational analytic with cross sectional design with total 52 schoolchildren. Sample was taken by multistage random sampling. Data was collected by measuring weight and height, 2x24 hours food recall, and PAQ-C. Data was analyzed using Pearson Correlation test. The result showed that there was a correlation between energy intake (p=0.003) and physical activity (p=0.003) with overnutrition. The conclusion of this study is that both intake of energy and physical activity have correlation to z-score of BMI for age in primary schoolchildren in rural area. The school need to provide nutrition education to increase knowledge of student about nutrition and also the guidance to parents regarding limiting the time for watching television and exercise regularly.Keywords: energy intake, overnutrition, physical activity, rural area